2010
DOI: 10.1208/s12249-010-9385-0
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Bioavailability Assessment of SMEDDS Containing Valsartan

Abstract: A self-microemulsifying drug delivery system (SMEDDS) has been developed to enhance diffusion rate and oral bioavailability of valsartan. The solubility of valsartan was checked in different oils, surfactants, and cosurfactants and ternary phase diagrams were constructed to evaluate the microemulsion domain. The valsartan SMEDDS was prepared using Capmul MCM (oil), Tween 80 (surfactant), and polyethylene glycol 400 (cosurfactant). The particle size distribution, zeta potential, and polydispersity index were de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
60
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(64 citation statements)
references
References 26 publications
3
60
0
Order By: Relevance
“…The purpose was to arrive at a composition that contained minimum amount of surfactant and co-surfactant without compromising its globule size and stability (9). From Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The purpose was to arrive at a composition that contained minimum amount of surfactant and co-surfactant without compromising its globule size and stability (9). From Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To determine the concentration of SMEDDS components that resulted in maximum microemulsion existence area, pseudoternary phase diagrams were constructed employing the water titration method at ambient temperature (25°C) (9). Mixtures of surfactant and co--surfactant (S mix ) in different ratios by mass (1:1, 1:2, 2:1) were prepared.…”
Section: Ternary Phase Diagrammentioning
confidence: 99%
“…1 After oral administration of a capsule (VST 80 mg), absolute bioavailability (BA) of VST was relatively low at ~23%, which might be due to the limited solubility in water and acidic pH of the stomach. 2 In order to enhance the solubility and oral absorption of VST, various formulation approaches, such as solid dispersion, spray-dried emulsion, spray-dried nanosuspension, and supercritical antisolvent process, have been studied. [3][4][5][6] Self-microemulsifying drug delivery systems (SMEDDS) are widely known to overcome low solubility and poor oral absorption of water-insoluble drugs.…”
Section: Introductionmentioning
confidence: 99%
“…[22] Several studies have been published reporting MC glycerides for developing SEDDS of a wide variety of drugs. [23][24][25][26] According to these studies, being small molecular volume oil phase, medium chain glycerides showed the high solvent capacity and excellent miscibility with other surfactants and co-surfactants and enhanced the permeability and bioavailability of candidate drugs. While SCT, such as Triacetin, has not been widely explored for preparing SMEDDS.…”
Section: Original Articlementioning
confidence: 99%